2022
DOI: 10.1186/s13054-022-04053-6
|View full text |Cite
|
Sign up to set email alerts
|

Key characteristics impacting survival of COVID-19 extracorporeal membrane oxygenation

Abstract: Background Severe COVID-19 induced acute respiratory distress syndrome (ARDS) often requires extracorporeal membrane oxygenation (ECMO). Recent German health insurance data revealed low ICU survival rates. Patient characteristics and experience of the ECMO center may determine intensive care unit (ICU) survival. The current study aimed to identify factors affecting ICU survival of COVID-19 ECMO patients. Methods 673 COVID-19 ARDS ECMO patients trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 35 publications
2
24
0
Order By: Relevance
“…Comparable mortality rates of up to 71 % in critically ill COVID-19 patients with vvECMO therapy were already observed in a large nation-wide German study with over 10,000 COVID-19 patients [ 30 ]. Accordingly, the analyses of an observational study at 26 German ECMO centers show that in high-volume centers such as ours (defined as specialized ECMO centers with more than 50 vvECMO therapies in 2019) 38% of COVID-19 vvECMO patients survived [ 31 ]. The timing of BChE measurement during SARS-CoV-2 infection in this study is a crucial factor for the interpretation of our data: previous studies evaluated BChE early in acute inflammatory entities, while most COVID-19 patients in our study may have been infected with SARS-CoV-2 for weeks and had already been treated in other intensive care units for several days before being transferred to our department.…”
Section: Discussionmentioning
confidence: 99%
“…Comparable mortality rates of up to 71 % in critically ill COVID-19 patients with vvECMO therapy were already observed in a large nation-wide German study with over 10,000 COVID-19 patients [ 30 ]. Accordingly, the analyses of an observational study at 26 German ECMO centers show that in high-volume centers such as ours (defined as specialized ECMO centers with more than 50 vvECMO therapies in 2019) 38% of COVID-19 vvECMO patients survived [ 31 ]. The timing of BChE measurement during SARS-CoV-2 infection in this study is a crucial factor for the interpretation of our data: previous studies evaluated BChE early in acute inflammatory entities, while most COVID-19 patients in our study may have been infected with SARS-CoV-2 for weeks and had already been treated in other intensive care units for several days before being transferred to our department.…”
Section: Discussionmentioning
confidence: 99%
“…The outcome data for the retrievals do not significantly differ from the in-house cannulations. A comparison to the systems with a proportional reimbursement for care not regulated by medical societies and medical insurance [ 31 ] has been demonstrated particularly during the pandemic of SARS-CoV-2 [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“… 32 , 33 The other study showed that BMI <24.9 kg/m 2 was associated with increased mortality risk. 34 This may indicate that BMI had an effect on the prognosis of infectious diseases. In our study, BMI <18.5 kg/m 2 was a protective factor of 90-day death for immunosuppressed elderly people (OR: 0.307, 95%CI: 0.130–0.723, p =0.007).…”
Section: Discussionmentioning
confidence: 99%